Filomela, słowik i poeta. O Naruszewiczowskim przekładzie ody Jeana‑Baptiste’a Rousseau - Dąbrowski, Roman (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article is devoted to the analysis of the poem by Adam Naruszewicz Duma do słowika that is the translation of the ode by Jean‑Baptise Rousseau, A Philomele. The poem’s narrative order is marked out by the comparison of the two texts; and all that is done to show the way Polish poet rendered the original text. In the article particular attention is paid to the differences between fragments of the French work and Polish Duma do słowika. But above all, the analysis brings out the fact that Naruszewicz’s style was quite distinct, and the relation of lyrical I to the recipient of the utterance is slightly different from that in the Rousseau’s poem, which is particularly noticeable in the ending passage of the Polish work. Important features of the Naruszewicz‑as‑a‑translator’s technique are also discussed.